Bryophytes of the Cerrado: a floristic study in an urban area and in two conservation units in eastern Maranhão, Brazil - Francimária Vasconcelos Carvalho; José Augusto dos Santos Silva; Anna Luiza Ilkiu-Borges; Denise Pinheiro Costa; Rozijane Santos Fernandes (Check List)
Bryophyte studies in the Cerrado Maranhense over the last five years have revealed 42 newly recorded species of bryophytes. Although the highest concentration of studies have been undertaken in east‑ ern Maranhão, there are still areas there that have not been inventoried, such as the conservation units in the municipality of Chapadinha. Herein, we inventory the bryophytes in this municipality. Data were obtained from bryophyte specimens deposited in the herbarium Centro de Ciências Agrárias e Ambientais, Universidade Federal do Maranhão and additional material collected by us. We identified 303 specimens representing 54 species, which included two hornworts, 25 liverworts, and 27 mosses. Two species are newly reported from the state: Plagiochila subplana Lindenb. and Fissidens subulatus Mitt.; the distribution of the latter species is extended into the Brazilian Cerrado. Our study shows the importance of increasing sampling efforts for bryophytes in Maranhão and highlights the diversity of these Cerrado formations.